Factors Affecting Stunting in Merawang District, Bangka Regency - Hidayat, Taufik; Lidyawati, Lidyawati; Oktavia, Shela; Putra, Agung Rizki (MediaTrend, 2024)
This study focuses on analyzing the factors influencing Stunting occurrences in the Merawang Subdistrict, Bangka Regency. Stunting is a chronic nutritional deficiency condition that leads to impaired physical growth in children, as measured by height below age-standard norms. The research adopts an observational approach with a cross-sectional design to explore the relationship between parental education levels, occupation, family income, and early marriage with Stunting prevalence in the region. The study findings reveal that low parental education levels, particularly among mothers, are closely associated with an increased risk of Stunting in children. Additionally, parents working as daily wage laborers with uncertain incomes contribute to inadequate provision of nutritional intake. The research also identifies that low family income typically ranging from IDR 1,000,000 to IDR 2,000,000 per month limits access to nutritious food and adequate healthcare services. Surprisingly, early marriage does not show a significant correlation with Stunting occurrences in this area. The study underscores the importance of improving education and economic stability as crucial steps in combating Stunting. Efforts to raise awareness and enhance access to better education, along with economic interventions to boost family income, can be effectzive strategies for reducing Stunting prevalence in the Merawang Subsdistrict